Can Pharmacological Conditioning as an Add-On Treatment Optimize Standard Pharmacological Treatment in Patients with Recent-Onset Rheumatoid Arthritis? A Proof-of-Principle Randomized Clinical Trial - Meriem Manaï; Henriët van Middendorp; Joy A. van der Pol; Cornelia F. Allaart; Elise Dusseldorp; Dieuwke S. Veldhuijzen; Tom W. J. Huizinga; Andrea W. M. Evers (MDPI AG, 2024)
Medication regimens using conditioning via variable reinforcement have shown similar or improved therapeutic effects as full pharmacological treatment, but evidence in patient populations is scarce. This proof-of-principle double-blind randomized clinical trial examined whether treatment effects in recent-onset rheumatoid arthritis (RA) can be optimized through pharmacological conditioning. After four months of standardized treatment (n = 46), patients in clinical remission (n = 19) were randomized to the Control group (C), continuing standardized treatment (n = 8), or the Pharmacological Conditioning (PC) group, receiving variable treatment according to conditioning principles (n = 11). After eight months, treatment was tapered and discontinued linearly (C) or variably (PC). Standard treatment led to large improvements in disease activity and HRQoL in both groups. The groups did not differ in the percentage of drug-free clinical remission obtained after conditioning or continued standard treatment. The PC group did show a larger decrease in self-reported disease activity (Cohen's d = 0.9) and a smaller increase in TNF-α levels (Cohen's d = 0.7) than the C group. During all phases, more differences between groups were found for the patients who followed protocol than for the intention-to-treat sample. Although the results are not conclusive, pharmacological conditioning may have some advantages in terms of disease progression and stability, especially during the conditioning phase, compared with standard clinical treatment. The effects may be particularly beneficial for patients who show a good initial response to increased medication dosages.